Aneurisma de aorta abdominal na infância - Abdo Farret Neto; Jeancarlo Fernandes Cavalcante; Renato Vilar Furtado (Revista do Colégio Brasileiro de Cirurgiões)
The authors report a case of an abdominal aortic aneurism involving all visceral branches minus the Inferior Mesenteric artery in a 4-year-old girl. There was sugestive evidence that the arterial disease had an inflamatory or infectious etiologic factor. The most probable etiological factors could be salmonelas infection of the arterial wall or Takayasu's disease secondary to tuberculosis. The treatment with antibiotic to salmonelas infection during ten days, followed by tuberculostatic therapy for six months was chosen. Concerning the age, the arteries involved and the inflamatory aspect of the aneurysm, the surgical option became an alternative to the clinic treatment in case of any future evidence of the aneurysm enlargement. The patient became asymptomatic as soon as the antibiotic has been started. The control of the aneurysm evolution will be made by ecography each three months.